Implementasi Metode OMAX Dalam Meningkatkan Produktivitas Kinerja Perusahaan Pada UKM Tas Kulit - Andri Herlambang; Yuli Setiawannie; Nita Marikena (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Measuring the company level of productivity performance is a very important thing to do to see and evaluate achievements and improvements to productivity levels that are not yet optimal. This case study was taken from the leather bag UKM which is currently experiencing a decline in productivity during the 2020 period. With the increase in working hours, the company must increase workers' overtime costs. In this research, the method used to measure the level of company productivity is the objective matrix or OMAX method and this research refers to the OMAX steps, namely determining productivity criteria on the production line, determining weights, determining levels on the objective matrix, calculating the productivity index, and productivity analysis with a traffic light system. The research results show that the average value of overall productivity in 2020 is 4,388 The highest productivity index was achieved in August amounting to 67,01%. From the traffic light system, it is known that the worst indicator of productivity is the defect factor, so improvements need to be made regarding this.